(x-1)^2-16=-12
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 1 + 1/4 + 1/8 + 1/16
= 16/16 + 4/16 + 2/16 + 1/16
= 23/16
b) 2 - 1/8 - 1/12 - 1/16
= 96/48 - 6/46 - 4/48 - 3/48
= 83/48
c) 4/99 × 18/5 : 12/11 + 3/5
= 8/55 : 12/11 + 3/5
= 2/15 + 3/5
= 2/15 + 9/15
= 11/15
d) (1 - 3/4) × (1 + 1/3) : (1 - 1/3)
= 1/4 × 4/3 : 2/3
= 1/3 : 2/3
= 2
`@` `\text {Ans}`
`\downarrow`
`1,`
`a)`
`5 \times 72 \times 10 \times 2`
`= 5 \times 2 \times 10 \times 72`
`= 10 \times 10 \times 72`
`= 100 \times 72`
`= 7200`
`b)`
`40 \times 125`
`= 4 \times 10 \times 25 \times 5`
`= (5 \times 10) \times (4 \times 25)`
`= 50 \times 100`
`= 5000`
`c)`
`4 \times 2021 \times 25`
`= (4 \times 25) \times 2021`
`= 100 \times 2021`
`= 202100`
`d)`
`16 \times 6 \times 25`
`= 4 \times 4 \times 6 \times 25`
`= (4 \times 25) \times 4 \times 6`
`= 100 \times 24`
`= 2400`
`2,`
`a)`
`24 \times 57 + 43 \times 24`
`= 24 \times (57+43)`
`= 24 \times 100`
`= 2400`
`b)`
`12 \times 19 + 80 \times 12 +12`
`= 12 \times (19 + 80 + 1)`
`= 12 \times 100`
`= 1200`
`c)`
`(36 \times 15 \times 169) \div (5 \times 18 \times 13)`
`= 36 \times 15 \times 169 \div 5 \div 18 \div 13`
`= 6 \times 6 \times 3 \times 5 \times 13 \times 13 \div 5 \div 3 \times 6 \div 13`
`= (6 \div 6) \times (3 \div 3) \times (5 \div 5) \times (13 \div 13) \times 6 \times 13`
`= 6 \times 13`
`= 78`
`d)`
`(44 \times 52 \times 60) \div ( 11 \times 13 \times 15)`
`= 44 \times 52 \times 60 \div 11 \div 13 \div 15`
`= 4 \times 11 \times 13 \times 4 \times 15 \times 4 \div 11 \div 13 \div 15`
`= (11 \div 11) \times (13 \div 13) \times (15 \div 15) \times 4 \times 4 \times`
`= 4 \times 4 \times 4`
`= 64`
`3,`
`a)`
`x - 280 \div 35 = 5 \times 54`
`x - 8 = 270`
`x = 270 + 8`
`x = 278`
`b)`
`(x - 280) \div 35 = 54 \div 4`
`(x - 280) \div 35 = 13,5`
`x - 280 = 13,5 \times 35`
`x - 280 = 472,5`
`x = 472,5 + 280`
`x = 752,5`
`c)`
`(x - 128 + 20) \div 192 = 0`
`x - 128 + 20 = 0 \times 192`
`x - 128 + 20 = 0`
`x - 108 = 0`
`x = 0 + 108`
`x = 108`
`d)`
`4 \times (x + 200) = 460 + 85 \times 4`
`4 \times (x+200) = 460 + 340`
`4 \times (x+200) = 800`
`x + 200 = 800 \div 4`
`x + 200 = 200`
`x = 200 - 200`
`x = 0`
`4,`
`a)`
`7/12 - 5/12`
`= (7 - 5)/12`
`= 2/12`
`= 1/6`
`b)`
`8/11 + 19/11`
`= (8+19)/11`
`= 27/11`
`c)`
`3/8 + 5/12`
`= 9/24 + 10/24`
`= 19/24`
`d)`
`3/4 + 7/12`
`= 9/12 + 7/12`
`= 16/12`
`= 4/3`
`5,`
`a)`
`x - 6/7 = 5/2`
`x = 5/2 + 6/7`
`x = 47/14`
`b)`
`12/7 \div x + 2/3 = 7/5`
`12/7 \div x = 7/5 - 2/3`
`12/7 \div x = 11/15`
`x = 12/7 \div 11/15`
`x = 180/77`
`@` `\text {Kaizuu lv uuu}`
Ta có :
= 2.[1/10.12+1/12.14+1/14.16+...+1/x.(x+2)] = 19/400 = 2/10.12+2/12.14+2/14.16+...+2/x.(x+2) = 19/400
Mà 2/10.12=1/10-1/12
2/12.14=1/12-1/14
............................................
= 1/10-1/12+1/12-1/14+...+1/x-1/x+2 = 19/400
= 1/10-1/x+2 = 19/400
=>1/x+2 = 1/10-19/400 => 1/x+2=21/400
42-2(x+16) +12 :2=6(x-1)+ (-4)^3 :16
42- 2x- 32 +6 = 6x - 6 - 64: 16
(42 - 32 +6) - 2x = 6x - 6 - 4
16 = 2x = 6x- 10
16+10= 2x+6x
26= 8x
x= 26/8
x= 13/4
a) \(\left(12-12\dfrac{1}{3}\right):x+\dfrac{1}{6}=-\dfrac{2}{3}\)
\(-\dfrac{1}{3}x=-\dfrac{2}{3}-\dfrac{1}{6}\)
\(-\dfrac{1}{3}x=-\dfrac{5}{6}\)
\(x=-\dfrac{5}{6}:\left(-\dfrac{1}{3}\right)\)
\(x=\dfrac{5}{2}\)
b) \(\dfrac{4}{x}=\dfrac{x}{16}\)
\(x^2=4.16\)
\(x^2=64\)
\(\Rightarrow x=8;x=-8\)
`a)=>(12-37/3):x+1/6=-2/3`
`=>(12-37/3):x=-5/6`
`=>(-1/3):x=-5/6`
`=>x=(-1/3):(-5/6)`
`=>x=6/15=2/5`
`b)4/x=x/16`
`=>x^2=4*16`
`=>x^2=64`
`=>x^2=(+-8)^2`
\(B=x^{17}-12.x^{16}+12.x^{15}-12.x^{14}+...-12.x^2+12x-1\)
\(=11^{17}-\left(11+1\right)11^{16}+\left(11+1\right)11^{15}-\left(11+1\right)11^{14}+...-\left(11+1\right)11^2+\left(11+1\right)11-1\)
\(=11^{17}-11^{17}-11^{16}+11^{16}+11^{15}-11^{15}-11^{14}+...-11^3-11^2+11^2+11-1\)
\(=11-1=10\)
Vậy B = 10
(\(x-1\))2 - 16 = - 12
(\(x-1\))2 = - 12 + 16
(\(x-1\))2 = 4
(\(x-1\))2 = 22
\(\left[{}\begin{matrix}x-1=-2\\x-1=2\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=-2+1\\x=2+1\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=-1\\x=3\end{matrix}\right.\)
Vậy \(x\) \(\in\) {-1; 3)
Mình đang cần gấp